2021
DOI: 10.3390/macromol1040017
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Synthesis of Poly(styrene-block-isobutylene-block-styrene) by TiCl4-Co-initiated Cationic Polymerization in Open Conditions

Abstract: The cationic polymerization of isobutylene and its block copolymerization with styrene using DiCumCl/TiCl4/2,6-lutidine initiating system has been studied in open conditions. It was shown that a higher concentration of proton trap is required in open conditions as compared to the glove box technique in order to have good control over molecular weight and polydispersity. Polyisobutylenes with Mn ≤ 50,000 g mol−1 and low polydispersity (Đ ≤ 1.2) were prepared at [Lu] = 12 mM. The synthesis of poly(styrene-block-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Initially, SIBS-2 with high molecular weight was six times stronger than SIBS-1, showed higher percentage of ultimate strain (28%, p < 0.01) and did not differ in Young’s modulus ( p = 0.99) ( Figure 6 e–g). This difference in tensile strength is consistent with the higher length of polystyrene side blocks in SIBS-2 (M n ~15,000 g mol −1 ) as compared to SIBS-1 (M n ~8700 g mol −1 ) [ 30 , 43 ]. Since SIBS belongs to the thermoplastic elastomer family, the increase in the length of “hard” polystyrene block results in the enhancement of interaction between polystyrene blocks of different polymer chains in polystyrene domains that, in turn, leads to the increase of tensile strength.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Initially, SIBS-2 with high molecular weight was six times stronger than SIBS-1, showed higher percentage of ultimate strain (28%, p < 0.01) and did not differ in Young’s modulus ( p = 0.99) ( Figure 6 e–g). This difference in tensile strength is consistent with the higher length of polystyrene side blocks in SIBS-2 (M n ~15,000 g mol −1 ) as compared to SIBS-1 (M n ~8700 g mol −1 ) [ 30 , 43 ]. Since SIBS belongs to the thermoplastic elastomer family, the increase in the length of “hard” polystyrene block results in the enhancement of interaction between polystyrene blocks of different polymer chains in polystyrene domains that, in turn, leads to the increase of tensile strength.…”
Section: Resultssupporting
confidence: 68%
“…In this study, two samples of SIBS were prepared by the sequential cationic polymerization of isobutylene and styrene with dicumyl chloride/TiCl 4 /2,6-lutidine initiating system following the protocol mentioned in our previous study [ 30 ]. Two triblock copolymer samples with similar content of styrene in the copolymer but different number-average molecular weight and, therefore, different length of both of blocks were prepared ( Table 1 , Figures S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, due to the high sensitivity of TiCl 4 to H 2 O, perfectly anhydrous conditions and invariable addition of a proton trap are required to suppress the undesirable initiation by protic impurities. 1,28,[34][35][36][37][38][39][40]44 Recently, Wu and co-workers reported a new FeCl 3 -based initiating system for the living cationic polymerization of isobutylene. It was particularly shown that the dicumyl chloride (DiCumCl)/FeCl 3 / i PrOH initiating system afforded difunctional polyisobutylenes with a controlled molecular weight (M n up to 25 000 g mol −1 ) as well as triblock copolymers of isobutylene with styrene.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the high sensitivity of TiCl 4 to H 2 O, perfectly anhydrous conditions and invariable addition of a proton trap are required to suppress the undesirable initiation by protic impurities. 1,28,34–40,44…”
Section: Introductionmentioning
confidence: 99%